Psychological characteristics of Japanese attitude toward COVID-19: Sanitary masks and “jishuku” (self-restriction) - Tsuneyuki Abe; Alexander E. Raevskiy (Национальный психологический журнал, 2020)
Relevance of the article. COVID-19 is a serious global problem, that humanity is facing today. Different countries provide various measures to confront the epidemic. But not only measures differ from country to country, but people’s attitude to this problem is also quite different. In Japan the number of victims is relatively low, and it can be suggested that several socio-psychological factors of the Japanese society underlie this phenomenon. Aim of the current research is to describe psychological measures of confronting COVID-19 in Japan, and to analyze religious, cultural and psychological features of the Japanese people, that could predeterminate the effectiveness of measures conducted by the Japanese government to confront the epidemic. Course of the research. Current article is devoted to the two main features of Japanese policy confronting COVID-19: sanitary masks and self-restriction policy (jishuku). The attitude of the Japanese people to the epidemic, and the measures conducted by the government are analyzed from psychological point of view. Also, basic social and psychological factors that supposedly helped to control the epidemic and the features of governmental policy in confronting COVID-19 are described. Results. Important feature of the Japan’s anti-COVID-19 policy was an absence of strict measures suppressing individual freedom. But in spite of that, government’s appeal for the mask use and social distance was carefully followed by the people. It can be probably explained by a historically based tendency of the Japanese people to conduct themselves in accordance with the social rules, a daily habit of sanitary masks usage, and also a special attitude to cleanliness and hygiene. Conclusion. Fight against COVID-19 requires systematic, coordinated and constructive approach, use of several scientific disciplines, human resources and technological solutions. Probably the Japanese experience in this problem would help international community to confront epidemic.